Concurrent Measurements of Soil and Ecosystem Respiration in a Mature Eucalypt Woodland: Advantages, Lessons, and Questions. Issue 3 (26th March 2021) - Renchon, A. A.; Drake, J. E.; Macdonald, C. A.; Sihi, D.; Hinko‐Najera, N.; Tjoelker, M. G.; Arndt, S. K.; Noh, N. J.; Davidson, E.; Pendall, E.
Abstract: Understanding seasonal and diurnal dynamics of ecosystem respiration (Reco ) in forests is challenging, because Reco can only be measured directly during night‐time by eddy‐covariance flux towers. Reco is the sum of soil respiration (Rsoil ) and above‐ground respiration (in theory, RAG  = Reco  − Rsoil ). Rsoil can be measured day and night and can provide a check of consistency on Reco, as the difference in magnitude and time dynamic between Reco and Rsoil should be explained by RAG . We assessed the temporal patterns and climatic drivers of Rsoil and Reco in a mature eucalypt woodland, using continuous measurements (only at night for Reco ) at half‐hourly resolution over 4 years (2014–2017). Our data showed large seasonal and diurnal (overnight) variation of Reco, while Rsoil had a low diurnal amplitude and their difference (Reco  − Rsoil, or RAG ) had a low seasonal amplitude. This result implies at first glance that seasonal variation of Reco was mainly influenced by Rsoil while its diurnal variation was mainly influenced by RAG . However, our analysis suggests that the night‐time Reco decline cannot realistically be explained by a decline of RAG . Chamber measurements of autotrophic components at half‐hourly time resolution are needed to quantify how much of the Reco decline overnight is due to declines in leaf or stem respiration, and how much is due to missing storage or advection, which may create a systematic bias in Reco measurements. Our findings emphasize the need for reconciling bottom‐up (via components measured with chambers) and direct estimates of Reco (via eddy‐covariance method). Plain Language Summary: Climate is changing rapidly, mostly because of increasing atmospheric CO2 resulting from human‐caused emissions. An important question regarding climate change mitigation is: will land continue to absorb human‐caused CO2 emissions? To address this question, the net exchange of CO2 between ecosystem and the atmosphere has been measured globally by a network of flux towers. Flux towers rely on a complex method, which has been continually improved in the last decades. One way to ensure the quality of these data is to measure the same CO2 fluxes using different and independent methods and test whether or not the estimates are similar. In this study, we measured the amount of CO2 emitted at night by a forest and its soil, using two different techniques. We found that, overnight, the time course of the measurements diverged. Further analysis showed that this difference could not be explained by biological mechanisms. Thus, there may be an error in the flux tower measurements of the CO2 emitted by the forest, owing to unaccounted‐for physical processes. We discussed what implication this measurement error has on the use of these data, and what future steps should be taken by the community to identify and correct this error. Key Points: Seasonal and diurnal dynamics of soil respiration were used to constrain ecosystem respiration over 4 years Overnight decline in ecosystem respiration could not be explained by soil or aboveground respiration, suggesting measurement bias Measurements of fluxes and temperature sensitivity of autotrophic respiration components are needed to reduce ecosystem scale uncertainty